Utilisation of numerical and experimental method in noise reduction of 2-stroke cycle gasoline engine - 236469 Roslan Abdul Rahman; Mazlan Zubair; Norsham Amin; Asia-Pacific Vibration Conference (10th : 2003 : Brisbane, Australia) (Skudai : Universiti Teknologi Malaysia, 2003)
20